Today was a Good Day: The Daily Life of Software Developers - Meyer, Andre N.; Barr, Earl T.; Bird, Christian; Zimmermann, Tom (IEEE Transactions on Software Engineering, 2019)
What is a good workday for a software developer? What is a typical workday? We seek to answer these two questions to learn how to make good days typical. Concretely, answering these questions will help to optimize development processes and select tools that increase job satisfaction and productivity. Our work adds to a large body of research on how software developers spend their time. We report the results from 5971 responses of professional developers at Microsoft, who reflected about what made their workdays good and typical, and self-reported about how they spent their time on various activities at work. We developed conceptual frameworks to help define and characterize developer workdays from two new perspectives: good and typical. Our analysis confirms some findings in previous work, including the fact that developers actually spend little time on development and developers’ aversion for meetings and interruptions. It also discovered new findings, such as that only 1.7% of survey responses mentioned emails as a reason for a bad workday, and that meetings and interruptions are only unproductive during development phases; during phases of planning, specification and release, they are common and constructive. One key finding is the importance of agency, developers’ control over their workday and whether it goes as planned or is disrupted by external factors. We present actionable recommendations for researchers and managers to prioritize process and tool improvements that make good workdays typical. For instance, in light of our finding on the importance of agency, we recommend that, where possible, managers empower developers to choose their tools and tasks.
To appear.